Engineering transkingdom signalling in plants to control gene expression in rhizosphere bacteria - Barney A. Geddes (Nature Portfolio, 2019)
The root microbiota is critical for promoting crop yield. Here, the authors create a synthetic pathway for the production of the rhizopine scyllo-inosamine in Medicago truncatula and barley, and show its perception by rhizosphere bacteria for targeted regulation of bacterial gene expression.